Engaging Students in Learning the Relations of Geographical Elements through GIS-Enabled Property Price Visualization - Chuanbing Wang; Daihu Yang; Huimin Xu (MDPI AG, 2022)
Understanding the relations of urban elements is important in secondary school geography. Based on the price data of 22,684 listed apartments, this article aims to enable students to understand how geographical elements are related to the distribution of apartment prices through spatial analysis using ArcGIS 10.8. The spatial analysis showed that apartment prices are related to their proximity to government offices, schools, hospitals and main traffic roads. The content analysis of field notes, interviews and discussions suggests that students favor geographic information system (GIS)-based teaching and feel geospatial technology is useful to visualize the relationship of apartment prices to other geographical elements. Moreover, GIS-based teaching not only improves students' skill of generating datasets and raster maps, but also provides more room for students' enquiries compared to conventional teaching.